Beneficial Microorganisms in Medical and Health Applications - Liong, Min-Tze.; Liong, Min-Tze. (Microbiology Monographs,, 2015)
This volume is devoted to the application of microorganisms in medical treatment and health protection. Topics discussed include the role of probiotics in immune modulation, in prevention of influenza, and in atopic dermatitis. Further chapters cover aspects such as the relation of the gut microbiome and stress, the immune system, the regulation of inflammation, the benefits of Bifidobacterium for infants, and bacteriocin in medical applications, as well as the use of in vitro models of the gastrointestinal tract, omics approaches for targeting microbial health potential and the production of hepatitis B vaccines. This volume will be of particular interest to scientists working in the fields of clinical medicine, applied microbiology, pharmacy and public health.